Spatiotemporal dynamics of benthic bacterial communities in the Perdido Fold Belt, Northwestern Gulf of Mexico - Sánchez-Soto, Ma. Fernanda; Cerqueda-García, Daniel; Aguirre-Macedo, M. Leopoldina; García-Maldonado, José Q. (Frontiers in Marine Science, 2023)
This study analyzed the spatiotemporal dynamics of surficial benthic microbial communities in a bathymetric gradient (44 - 3573 m) across four oceanographic campaigns at the Perdido Fold Belt (PFB) in the northwestern Gulf of Mexico (nwGoM). Bioinformatic analysis of 16S rRNA gene amplicons grouped the 27 samples into three clusters according to a longitudinal bathymetric gradient. Differences in community structure among clusters, based on PERMANOVA analysis, were partially explained by cruise, water depth, temperature, salinity, nitrate plus nitrite, silicate, redox potential, Ni, Cd, Pb, and Al, as well by aliphatic and aromatic hydrocarbon concentrations. Into microbial community composition, Gemmatimonadaceae, Planctomycetaceae, and the JTB255 were detected at all depths across the four campaigns. Members of Anaerolinaceae and specific sulfate-reducing bacteria were more abundant in sites located between 43 and 1200 m, and Rhodospirillaceae, wb1-A12, OM1 clade, Desulfurellaceae, Gemmatimonadetes, Nitrospinaceae, and Clostridiaceae 1 were better represented in deeper sites. Alpha diversity was similar between the three groups and remained stable; however, 10 samples presented changes in the community structure across the four campaigns. Finally, a multivariable association analysis revealed 25 bacterial genera positively related with physicochemical parameters that characterized the environment from shallow to deep sea sites. Taken together, these results yield insights into the temporal stability of 17 of 27 sites in the PFB and revealed signature taxa with putatively ecological relevance in sedimentary environments.